GRIND OF KING XERSES TO THE NATION IN 300 SPARTAN DIRECTED BY ZACK SNYDER (2007): A MARXIST APPROACH - JAYA , ADITYA RANGGA (2011)
The major problem of this research paper is how needs for Freedom and peacefulness. Is portrayed in Nation Spartan condition as which is oppressed people because factor power of king Xerses which wish to make Sparta people as slave, this matter influence the happening of grind manifestly which wish showed in this 300 Spartan movie based on Marxist Analysis. Thus, here the research analysis is focused on Leonidas and nation of Spartan as the major character. In this research, the writer is employs the qualitative method. In this method, the researcher uses two data sources which namely primary data and secondary data sources. The primary data source is 300 Spartan movies, the secondary data source are the books about Marxist, some books about Struggle, and another virtual references. Next, the other sources which are related to this analysis. The method of data collection is literary research and the technique of data collection is descriptive technique. Based on the analysis, the researcher draws two conclusions: first based on the structural analysis, the movie of Zack Snyder's 300 (2007) has united structural elements in which the structural elements are related one another. Second based on the Marxist analysis, Zack Snyder wants to reflect that freedom is the right of being Spartan nations. So, every people is entitled to get similar treatment in any forms.